KESETARAAN DAN KEADILAN SEBAGAI PRINSIP PENDIDIKAN ISLAM MULTIKULTURAL DI SEKOLAH DASAR - Maylia Khairunnisa Baher; Husnilawati; Heny Wulandari; Nilawati Tajudin; Chairul Amriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Equality and justice are fundamental principles in Islamic teachings that emphasize the dignity and equality of all human beings regardless of social, cultural, or ethnic backgrounds. In the context of Indonesia as a multicultural nation, these principles are highly relevant to be internalized through Islamic education, particularly at the elementary school level, where character formation begins. Islamic education in elementary schools plays a strategic role in shaping students’ attitudes toward diversity, tolerance, and social responsibility. This study aims to examine equality and justice as core principles of multicultural Islamic education in elementary schools. The research employs a qualitative library research method with a descriptive-analytical approach. Data were collected from various sources, including books, scientific journals, and relevant educational policy documents related to Islamic education and multiculturalism. The analysis reveals that the principles of equality and justice can be effectively implemented through the development of inclusive curricula that accommodate diverse student backgrounds, the application of humanistic and student-centered learning approaches, and the exemplary role of teachers in demonstrating fair and nondiscriminatory attitudes in classroom interactions. The study concludes that integrating equality and justice as foundational principles of multicultural Islamic education contributes to the development of tolerant, respectful, and socially aware students who are prepared to live harmoniously in a pluralistic society.